METHODOLOGY OF INTERPRETATION OF MUHAMMAD AMIN AL-SYINQITI - Sunantri, Sri; Abubakar, Achmad; Nawas, Kamaluddin Abu; Firdaus, Firdaus (Jurnal Adabiyah, 2020)
Interpretations of the modern period are very diverse in terms of methodology. One of them is a work of interpretation from Muhammad Amin al-Syinqiti with his monumental work Adwa’ Al-Bayan fi Idah al-Qur'an bi Al-Qur'an. Al-Syinqiti is a Maliki scholar active in the field of education and teaching, preacher and a judge. The interpretation aims to find the meanings, wisdom and laws contained in the Qur'an, and invite Muslims to return to the Qur'an in living their lives. This study describes the methodology of its interpretation which includes the general systematic interpretation, the methods used in interpreting the Qur'an include the methods of tahlili, Muqarin, and ijmali. The analysis of tahlili and muqa>rin on ayat al-ahkam, while the ijmali method in eschatological verses and verses of nature, other than ayat al-ahkam. The form of interpretation is bi al-ma’sur and bi al-ra’yi. The form of interpretation is inseparable from the sources it uses, namely originating in the Qur'an, hadith, qaul sahabah, ulama convention, poetry, and qira'at sab'ah. The interpretation of the Qur'an with the Qur'an (verse by verse) becomes dominant in its interpretation. While the interpretation style is fiqh and languages style.تختلف التفسيرات الحديثة بشكل كبير من وجهة نظر منهجية. واحد منهم هو عمل تفسير لمحمد عامي> ن Al-Syinqiti مع عمله الضخم Adwa 'al-Bayan fi Idah al-Qur'anbi al - القرع> ن. محمد عامي> n al-Syinqiti عالم من المذهب المالكي ناشط في مجالات التربية والتعليم وخطيب وقاضي. ويهدف التفسير إلى معرفة المعاني والحكمة والأحكام الواردة في القرآن ، ودعوة المسلمين للعودة إلى القرآن في عيش حياتهم. تصف هذه الدراسة منهجية التفسير الخاصة بها والتي تشمل المنهجيات العامة لتفسيره ، والطرق التي يستخدمها في تفسير القرآن ، بما في ذلك طرق التحلي ، والمقاء ، والإجماع. تحليل tahlili و muqa rin in ayat al-ahkam ، بينما طريقة ijma li في الآيات الأخروية وآيات الطبيعة ، بخلاف ayat al-ahkam. وشكل التفسير هو بالألم والرائع. لا يمكن فصل شكل التفسير عن المصادر التي يستخدمها ، والتي يتم الحصول عليها من القرآن ، والحديث ، وقلصحة ، وإجتهاد العلماء ، وسير ، وقيرة في الصباح. إن تفسير القرآن بالقرآن هو السائد في تفسيره. وفي الوقت نفسه ، يعتمد التفسير على الفقه واللغة.Penafsiran masa modern sangat beragam dari segi metodologi. Salah satunya adalah sebuah karya penafsiran dari Muhammad Amin al-Syinqiti dengan karya monumentalnya Adwa’ al-Bayan fi Idah al-Qur’an bi al-Qur’an. Muhammad Amin al-Syinqiti adalah seorang ulama bermazhab Maliki yang aktif pada bidang pendidikan dan pengajaran, pendakwah dan seorang hakim. Penafsirannya bertujuan untuk menemukan makna-makna, hikmah dan hukum-hukum yang terdapat dalam al-Qur’an, dan mengajak umat Islam kembali pada al-Qur’an dalam menjalani hidup. Kajian ini mendeskripsikan metodologi tafsirnya yang mencakup sistematika umum penafsirannya, metode yang digunakannya dalam menafsirkan al-Qur’an diantaranya metode tahlili, Muqarin, dan ijmali. Analisis tahlili dan muqarin pada ayat al-ahkam, sedangkan metode ijmali pada ayat eskatologis dan ayat-ayat sifat, selain ayat al-ahkam. Bentuk tafsirnya adalah bi al-ma’sur dan bi al-ra’yi. Bentuk penafsirannya tidak lepas dari sumber yang digunakannya, yakni bersumber pada al-Qur’an, hadis, qaul sahabah, ijtihad ulama, syair, dan qira’at sab’ah. Penafsiran al-Qur’an dengan al-Qur’an (ayat dengan ayat) menjadi dominan dalam penafsirannya. Sedangkan corak penafsirannya adalah corak fikih dan corak bahasa.